2005
DOI: 10.1137/s0895480103433409
|View full text |Cite
|
Sign up to set email alerts
|

Labeling Schemes for Small Distances in Trees

Abstract: We consider labeling schemes for trees, supporting various relationships between nodes at small distance. For instance, we show that given a tree T and an integer k we can assign labels to each node of T such that given the label of two nodes we can decide, from these two labels alone, if the distance between v and w is at most k and, if so, compute it. For trees with n nodes and k ≥ 2, we give a lower bound on the maximum label length of log n + Ω(log log n) bits, and for constant k, we give an upper bound of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(120 citation statements)
references
References 24 publications
3
117
0
Order By: Relevance
“…In the direct equivalence query problem, we give each element a unique label such that we can answer the equivalence query by computing directly from the two labels without using any auxiliary data except for the value of n. This problem was studied by Alstrup et al [2], where they showed that lg n + Θ(lg lg n) bits of space are necessary and sufficient to represent the labels. This bound was further strengthened by Lewenstein et al [16] to lg n + lg lg n + Θ(1)).…”
Section: Direct Equivalence Query Problemmentioning
confidence: 99%
See 3 more Smart Citations
“…In the direct equivalence query problem, we give each element a unique label such that we can answer the equivalence query by computing directly from the two labels without using any auxiliary data except for the value of n. This problem was studied by Alstrup et al [2], where they showed that lg n + Θ(lg lg n) bits of space are necessary and sufficient to represent the labels. This bound was further strengthened by Lewenstein et al [16] to lg n + lg lg n + Θ(1)).…”
Section: Direct Equivalence Query Problemmentioning
confidence: 99%
“…This problem has been studied by Katz et al [15], Alstrup et al [2], and Lewenstein et al [16]. Lewenstein et al [16] showed that with no auxiliary data structure, a label space of size n i=1 n i is necessary and sufficient to represent the equivalence relation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our focus is thus on informative labeling schemes using relatively short labels (say, of length polylogarithmic in n). Labeling schemes of this type were recently developed for different graph families and for a variety information types, including vertex adjacency [Alstrup and Rauhe 2002;Breuer 1966;Breuer and Folkman 1967;Kannan et al 1992;Korman et al 2006], distance [Alstrup et al 2005;Katz et al 2000;Kaplan and Milo 2001;Korman et al 2006;Peleg 1999;Thorup 2004], tree routing [Fraigniaud and Gavoille 2001;Fraigniaud and Gavoille 2002;Thorup and Zwick 2001], vertex-connectivity [Alstrup and Rauhe 2002;Katz et al 2004], flow Katz et al 2004], tree ancestry [Abiteboul at al. 2001;Abiteboul at al.…”
Section: Problem and Motivationmentioning
confidence: 99%